2003
DOI: 10.1016/s0003-6870(03)00009-7
|View full text |Cite
|
Sign up to set email alerts
|

Interface pressure data and the prediction of driver discomfort in road trials

Abstract: An objective measure that will predict discomfort reliably, and which can be used at an early stage in the development of a vehicle and its seating, would have the potential to reduce the prevalence of musculoskeletal problems associated with driving. This paper reports on an extended road trial study to further investigate the potential value of pressure distribution data in the prediction of reported discomfort. Road trial data were collected from three cars and then interface pressure data were recorded for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 9 publications
3
48
1
Order By: Relevance
“…Previous studies (e.g. El Falou et al, 2003;Porter et al, 2003;De Carvalho andCallaghan, 2011, Smith et al 2015) have shown analytically that sensation of overall discomfort increases over time. Through a series of studies involving motion and long-duration sitting, Mansfield et al (2014) showed that discomfort increases both with vibration magnitude and with sitting duration, and that the presence of vibration causes an increase in the rate of discomfort onset.…”
Section: Introductionmentioning
confidence: 91%
“…Previous studies (e.g. El Falou et al, 2003;Porter et al, 2003;De Carvalho andCallaghan, 2011, Smith et al 2015) have shown analytically that sensation of overall discomfort increases over time. Through a series of studies involving motion and long-duration sitting, Mansfield et al (2014) showed that discomfort increases both with vibration magnitude and with sitting duration, and that the presence of vibration causes an increase in the rate of discomfort onset.…”
Section: Introductionmentioning
confidence: 91%
“…Mansfield et al (2014) and Mansfield et al (2015) demonstrated that a 'showroom' or static analysis is not sufficient to asses a seat's comfort as it fails to encompass many of the other factors affecting overall car seat discomfort. Porter et al (2003) demonstrated that short term evaluations of discomfort are inadequate as the effects of fatigue and long term sitting have not been accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…During sitting, discomfort increases through time. Porter et al [26] reported an increase in discomfort during driving road trials of 135 minutes sitting in a car seat. Smulders et al [8], indicated that the discomfort in an airline business class seat increases in time.…”
Section: Environmental Experiences Through Timementioning
confidence: 99%